2016
DOI: 10.3390/en9050351
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Damage Induced Gas Flow Pattern and Permeability Variation of Coal from Songzao Coalfield in Southwest China

Abstract: Abstract:The permeability of coal is a critical parameter in estimating the performance of coal reservoirs. Darcy's law describes the flow pattern that the permeability has a linear relationship with the flow velocity. However, the stress induced deformation and damage can significantly influence the gas flow pattern and permeability of coal. Coals from Songzao coalfield in Chongqing, southwest China were collected for the study. The gas flow velocities under different injection gas pressures and effective str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Pressure gradient was once considered as the driving force behind the migration of free gas in coal matrices. Li et al reported that there was a strong correlation between the permeability of coal reservoirs and the square of pressure gradients . Airey suggested long ago that gas desorbing from crushed coals should obey Darcy’s law .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pressure gradient was once considered as the driving force behind the migration of free gas in coal matrices. Li et al reported that there was a strong correlation between the permeability of coal reservoirs and the square of pressure gradients . Airey suggested long ago that gas desorbing from crushed coals should obey Darcy’s law .…”
Section: Introductionsupporting
confidence: 89%
“…Li et al reported that there was a strong correlation between the permeability of coal reservoirs and the square of pressure gradients. 36 Airey suggested long ago that gas desorbing from crushed coals should obey Darcy's law. 37 Our previous work had further demonstrated this viewpoint, 38 in which the whole adsorption process of each coal sample was consistent with Darcy's simulated curves, but there were still some noticeable flaws.…”
Section: Introductionmentioning
confidence: 99%